Clinical and Pharmacological Approaches to Optimize Outpatient Treatment of Bronchial Asthma - Olga Pashanova (Journal of Global Pharma Technology, 2016)
Asthma is a common chronic disease. There is no age-related predisposition to the disease, occurring in both adults and children. The study presents clinical trial of ANAFERON FOR CHILDREN® effect on URTI remission process in combination with mild and moderate bronchial asthma in children. The studies were based on a sample of 150 children (age 3-6 years, average age 4.1 ± 0.1), conducted during 2017-2019 in Moscow, the Russian Federation. The first group included 89 children taking ANAFERON once a day for 3 months; the second (control) group included the remaining 61 who took a placebo-treatment during the same time period. The presence of an autoimmune disease was an exclusion criterion. Significant difference of 2.5 times less occurring of the disease (p = 0.0002) was found between the average number for the experimental group compering to the control. Children from the experimental group were 2.2 times less likely to have exacerbations of bronchial asthma (p = 0.013). 3 days is the duration and maintenance period of symptoms for the experimental group, that’s 3 times lower comparing to the control group-9 days (p = 0.041). The Mean Neutrophil Volume (MNV) was significantly reduced (p = 0.001), in a month, Squamous Epithelium Index (SEI) (p = 0.009) in the experimental group. The experimental group maintained significantly low values of MNV and DRE at the end of ANAFERON therapy (p = 0.001). Current management of bronchial asthma includes a Treatment Effectiveness Assessment (TEA) and Patient Safety with medications prescribed, as well as improving of therapeutic cooperation and the patients’ quality of life. The use of ANAFERON reduces the frequency of URTI by 2.4 times in the 3-6-year-old children with bronchial asthma. Additionally, ANAFERON is well tolerated for children. The use of ANAFERON (as a preventive drug) reduces 1) occurring of mild and moderate bronchial asthma by 1.5 times; 2) the number of cases of bronchial asthma exacerbation by 2.2 times; 3) the duration of asthmatic attacks by 3 times. This is associated with cytoprotective effect of the drug on the olfactory epithelium, as well as its influence on reducing the number of children with low IFNƛ (by 3.4 times in 3 months of therapy). Keywords: Bronchial asthma, Prevention, ANAFERON, Placebo, Cytological indicators.